Between hope and future planning: the dementia journey for care partners through the lens of relational autonomy - Alixe Ménard; Adebusola Adekoya; Elizabeth Birchall; Kishore Seetharaman; Lucy Kervin; Koushambhi Khan; Jennifer Baumbusch (BMC Medical Ethics)
Abstract Background Future planning is essential for care partners to discuss and prepare for the goals of care for their relatives living with dementia. However, engaging in these discussions can be particularly challenging as care partners navigate the unpredictable and uncertain trajectory of dementia. This study aimed to explore how care partners of persons living with dementia engage in future planning (or not) throughout the dementia journey. Methods This multi-method qualitative study used a relational autonomy framework to examine the experiences of care partners providing daily care to a person living with dementia. Fifteen care partners from British Columbia, Canada, participated in semi-structured interviews and maintained reflective diaries over a period of up to two years (August 2020–October 2023). Data were analyzed using thematic analysis to identify patterns and themes related to future planning. Results Four key themes were identified through the analysis: (1) changes to living arrangements, as care partners adjusted to the evolving needs of their relatives; (2) anticipatory grief, reflecting the emotional impact of witnessing the progression of dementia; (3) future planning with changing health, highlighting the challenges of aligning care plans with the shifting health status of the person living with dementia; and (4) finding hope, as care partners sought meaning and optimism amidst uncertainty. Conclusions This study underscores the complex and dynamic nature of future planning for care partners of individuals with progressive dementias. The findings highlight the need for tailored resources and interventions to support care partners in navigating future planning discussions, particularly in light of the emotional and relational challenges they face. Developing such resources could improve the preparedness and well-being of care partners as they engage in this critical aspect of caregiving.